Implementasi Keamanan Akses Terhadap Website Menggunakan Wireguard VPN Di Routerboard Mikrotik - Dian Novianto; Yohanes Setiawan Japriadi; Lukas Tommy (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
The need for the availability of information is currently very high, especially in the conditions of the COVID-19 pandemic, all organizational activities are carried out online. Human dependence on the role of information technology is increasing and this has consequences for long distance communication between devices, which requires users to be authenticated for access rights granted by the system. The problem that arises is the security of data travel during the authentication process, where there is the possibility of leaking account information. This is because communication is done on a public network while accessing resources that require privacy. Therefore we need a network connection that is safe and efficient. Virtual Private Network (VPN) is a network communication technology that allows you to connect to public networks safely and quickly. The VPN used in the solution to this problem is Wireguard. Wireguard is a VPN protocol built with advanced cryptography and makes it extremely fast and secure. The method used by the author in developing this system is PPDIOO which consists of, Prepare, Plan, Design, Implement, Operate, and Optimize. And also some supporting tools for the development of the system Unified Modeling Language. By using Wireguard VPN, the expected result is the security of the data sent to be more secure and can connect two remote networks privately using the public internet.Keywords : VPN, Wireguard, Mikrotik